Social life documents referring to tourism as a means to create local memory German language - Olszewska, Izabela (Acta Universitatis Lodziensis. Folia Germanica, 2018)
Local memory is a type of common memory and originates from memory studies. It defines a group’s memory, as it is ascribed to specific members of a community, specific places and time. Social life documents are carriers of popular information on specific memory places (i.e. places in a given regional space, as well as events, characters, artefacts) of a given region. From the point of view of time lapsing apart from a medium of communication they become a medium of local memory. The aim of the article is to analyse texts of social life documents referring to tourism as a medium creating local identity in the period of the Free City of Gdansk.